Analysis of the International Court of Justice’s Jurisdiction in the Airspace Violation Cases - Yordan Gunawan; Amarta Yasyhini Ilka Haque; Nazella Jeanny Andrian; Moli Aya Mina Rahma (Jambura Law Review, 2023)
This writing examines the International Court of Justice's authority over cases of airspace breaches. Airspace is the space above the land area and waters of a country. Air space is one of the most critical parts of a region in realizing the welfare of a country. ICJ, as the Supreme Court of the United Nations, is capable of resolving conflicts between countries and disputes involving United Nations member states. As a result, this writing aims to analyse further the authority of the International Court of Justice regarding airspace violations. The research was normative and qualitative. The result showed that, in theory, ICJ had clear jurisdiction in resolving violation of airspace cases, but in practice, only a few cases had been resolved by ICJ. However, most of those cases submitted to ICJ produce no judgment from ICJ since the Court found that it lacks jurisdiction